Partisipasi Masyarakat dalam Program Urban Farming Gang Hijau di RW 03 Kelurahan Cempaka Putih Timur, Jakarta - PERMATASARI, ENI; PARINING, NYOMAN; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Community Participation in the Urban Farming Program Gang Hijau at RW 03 Kelurahan Cempaka Putih Timur, Jakarta The trend of population growth in urban areas is very rapid, it is estimated that by 2025 there will be around 68% of Indonesia's population living in cities. Population growth due to urbanization creates new problems, namely the amount of food availability decreases and air pollution increases. The urban farming program Gang Hijau is an agricultural program designed by the DKI Jakarta Provincial Government which is suitable to be applied in urban areas because it does not require large tracts of land for its application. Community participation is needed to achieve the objectives of the urban agriculture program. This research was conducted with the aim of expressing community participation in the implementation and enjoying the results of the Green Gang urban farming program. This research was conducted in the area of ??RW 03, Kelurahan Cempaka Putih Timur by taking a sample of 44 people using the probability sampling method, which is simple random sampling. Data analysis method used is qualitative descriptive analysis. The results showed that the overall community participation in the urban farming program of the Gang Hijau in the RW 03 area is in the high category assessed based on the combined score between participation at the stage of implementation. Physical participation and non-physical participation and participation at the stage of enjoying the outcome with three aspects of social aspects, economic aspects and environmental aspects.